2017
DOI: 10.1002/anie.201710234
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methylammonium Iodide on the Supersaturation and Interfacial Energy of the Crystallization of Methylammonium Lead Triiodide Single Crystals

Abstract: It is very important to study the crystallization of hybrid organic-inorganic perovskites because their thin films are usually prepared from solution. The investigation on the growth of perovskite films is however limited by their polycrystallinity. In this work, methylammonium lead triiodide single crystals grown from solutions with different methylammonium iodide (MAI):lead iodide (PbI ) ratios were investigated. We observed a V-shaped dependence of the crystallization onset temperature on the MAI:PbI ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The accelerating dissolution of perovskite precursor salts should be expected due to the presence of complexation between PbI 2 and I − in precursor solution . However, it is reported that the size of colloids clusters in perovskite precursor solution prepared in GBL decreased with the increase of temperature due to the release of free ions into the solutions, leading to the shift of the equilibrium of the chemical reaction to the conversion of low‐order iodoplumbates of Pb 3 − and PbI 2 . Nevertheless, the precursor solution aging time seems to become a critical factor in determining the size and structure of colloid clusters in the precursor solutions.…”
Section: Colloidal Characteristics Of Perovskite Precursor Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accelerating dissolution of perovskite precursor salts should be expected due to the presence of complexation between PbI 2 and I − in precursor solution . However, it is reported that the size of colloids clusters in perovskite precursor solution prepared in GBL decreased with the increase of temperature due to the release of free ions into the solutions, leading to the shift of the equilibrium of the chemical reaction to the conversion of low‐order iodoplumbates of Pb 3 − and PbI 2 . Nevertheless, the precursor solution aging time seems to become a critical factor in determining the size and structure of colloid clusters in the precursor solutions.…”
Section: Colloidal Characteristics Of Perovskite Precursor Solutionsmentioning
confidence: 99%
“…Due to the chemical equilibrium between iodoplumbate coordination complexes and the competition among I − , solvent molecules, and additive to interact with Pb 2+ , the nature of perovskite precursor solution is sensitive to the temperature, components, and aging . In general, heating the precursor solution for extended duration at a mild temperature (70–180 °C) is suggested to fully dissolve the perovskite salts 73a.…”
Section: Colloidal Characteristics Of Perovskite Precursor Solutionsmentioning
confidence: 99%
“…The observation clearly indicates high immiscibility between MAI and SAN. Considering the measured contact angle (∼24°), the dispersive component of the surface tension for SAN (0.036 J/m 2 ), the estimated surface tension of MAI (0.2 J/m 2 ), and Young’s equation, we find that the interfacial tension γ between SAN and MAI are estimated to be ∼0.15 J/m 2 ; this very large surface tension is then equivalent to χ >10 based on the Helfand–Tagami equation, thus confirming that MAI and SAN are highly immiscible.…”
Section: Discussionmentioning
confidence: 53%
“…Single crystal perovskites are especially important as they have longer charge diffusion lengths, , higher carrier mobilities, , higher optoelectronic performance than thin film analogues, , and the atomic structures obtained via single-crystal X-ray diffraction are a starting point for first-principles simulations. Predicting perovskite crystallization is difficult because the precursor solutions are concentrated, nonideal electrolytes, subject to reagent compositional variation, , and sensitive to potentially uncontrolled experimental conditions such as temperature and humidity . As a result, most efforts to grow novel perovskite single crystals proceed through trial and error.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting perovskite crystallization is difficult because the precursor solutions are concentrated, nonideal electrolytes, 25−27 subject to reagent compositional variation, 28,29 and sensitive to potentially uncontrolled experimental conditions such as temperature and humidity. 30 As a result, most efforts to grow novel perovskite single crystals proceed through trial and error.…”
Section: ■ Introductionmentioning
confidence: 99%